An attempt of motion evaluation on the out-of-water arm recovery in the crawl stroke - Nagai, C.; Doki, H.; Saitou, K. (Japanese Journal of Sciences in Swimming and Water Exercise, 2004)
In this study, we propose the new technique to evaluate qualitatively the recovery motion of the arm in the crawl stroke which is the most fundamental swimming style. The recovery motion of the arm can be measured by the motion analysis using video camera. On the basis of the measuring result, the dynamic analysis is carried out using the 7-degree-of-freedom rigid body model on the upper limbs. By evaluating the load which affects the each arm joint from joint torque and joint force, and obtaining the power which shows the energy consumption of the joint, motion evaluation of some recovery actions is quantitatively carried out. Our evaluation method will be useful for improvement of training and guidance methods in swimming.